The role of membrane phospholipids in the implementation of protective strategies of bacteria - B. G. Andryukov; I. N. Lyapun; E. V. Matosova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
To maintain viability under stressful conditions of existence and the implementation of protective strategies, bacteria must receive signals and respond quickly to extreme changes in environmental parameters. The results of recent experimental studies complement the paradigm that has dominated since the 1970s on the predominant role of phospholipids (PL) as molecular building blocks in the formation of the cell wall of bacteria. Specific transformations of these lipid domains have shown to have a significant effect on the shape and function of cells, membrane remodeling, and the ability of bacteria to adapt to environmental stresses. The physiological role of bacterial PLs is pleiotropic and determines both cell integrity and cell function. In addition to the key structural role of membrane PL in the cell, their intermediate metabolites are able to act as secondary messengers and perform important signaling and regulatory functions. Modern studies of the mechanisms of detection and integration of signals from the environment that cause stationary-dynamic changes in phospholipid homeostasis and form pleiotropic resistant cellular bacterial phenotypes are of fundamental and practical interest. PL homeostasis was proved to be crucial for the pathogenesis of bacterial infections and is necessary not only to maintain the viability of bacteria, but also to ensure their growth during infection. The suppression of the biosynthesis of these macromolecules reduces the viability of bacteria. In recent decades, one of the main advances in the concept of "liquid mosaic" model of biological membranes has been the understanding of their domain structure. This discovery is of fundamental and practical interest, since phospholipid domains are a promising target for modern antimicrobial strategies. The aim of this review is to summarize modern ideas about the structural, metabolic and signaling role of membrane PL in the implementation of the protective mechanisms of bacteria and maintaining their viability in adverse environmental conditions.